Studies on health care and milking practices adopted at buffalo farms of peri urban area of Surat city, India - Sabapara, Ghanshyam Prabhulal; Kharadi, Vishnubhai Bhikabhai (Buffalo Bulletin, 2021)
A field survey was undertaken to collect the health care and milking management practices opted by randomly selected 50 buffaloes farm owners in peri urban areas of Surat city and data were collected by using personal interview schedule. The present study indicated that regular vaccination and deworming practice adopted by 96% and 38% of the respondents, respectively. Only 20% of respondents did not adopted control of ecto-parasites practices. Only 38% of respondents treated their sick buffalo by veterinary officer. Majority (58%) of respondents did not followed grooming practice to their buffaloes. Sick buffalo isolated from healthy one was adopted by only 12% of respondents. All the respondents’ clean udder and teats, wash their hands before milking and milked their animals at same place twice a day. Dry hand and full hand methods of milking was adopted by 24% and 18% of respondents, respectively. The use of oxytocin injection for letdown of milk after death of buffalo calf was adopted by 44% of respondents. Wipe the udder and teats after milking, teat dipping, testing for mastitis and teat canal sealing at the end of lactation was not practiced by any of the respondents.